SOSIALISASI TEKNIK PENYIMPANAN PRODUK HASIL TANGKAPAN LAUT DENGAN METODE BEKU DI DESA PENYAK - Fitri Afriani; Yekti Widyaningrum; Widodo Budi Kurniawan; Herman Aldila; Yuant Tiandho (Journal of Appropriate Technology for Community Services, 2020)
In this paper, the location that is targeted for community service activities is Penyak Village, Koba Sub-District, Central Bangka Regency. The majority of the profession of the Penyak Village community are fishermen because the village is directly adjacent to the South China Sea. Maritime resources in Penyak Village are quite abundant including various types of fish, shellfish and small crab. But most people who market these resources have not used techniques for storing fishery products. Therefore, it is feared that the fishery products will decline in quality. The solution offered to this community service is the socialization of frozen fishery product storage. In addition, in order for the community to directly utilize it, the freezer box equipment was provided to Penyak Village. Through the evaluation process, it is known that the freezer box provided can be utilized by Penyak Village community, especially for storing food products.